Implementation of Mobile Seamless Learning in Improving Learning Activity and Learning Achievement Students of SMP Negeri 1 Gemolong Sragen During the Period Pandemic - Wiwin Wulandari; Budi Murtiyasa (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
The purpose of this study is to determine the results of the implementation of mobile seamless learning in increasing the learning activity and learning achievement of students at SMP Negeri 1 Gemolong Sragen during the pandemic. This study uses a quasi-experimental method, using quantitative data analysis. The location of the study was carried out at SMP Negeri 1 Gemolong Sragen. The population in the study were all students of SMP Negeri 1 Gemolong Sragen. The sampling technique used Random Sampling where each class contained 32 students. The technique applied in this study is to use multiple choice and oral tests. In conducting the test, the validity test uses the product moment and the rehabilitation test uses the KR 20 formula. The data is then analyzed using normality and homogeneity tests. The results of the study indicate that there is an influence of mobile seamless learning on the learning activity and learning achievement of students of SMP Negeri 1 Gemolong Sragen During the Pandemic.